2021
DOI: 10.1038/s41380-021-01386-6
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin and pregabalin in bipolar disorder, anxiety states, and insomnia: Systematic review, meta-analysis, and rationale

Abstract: The gabapentinoids, gabapentin, and pregabalin, target the α2δ subunits of voltage-gated calcium channels. Initially licensed for pain and seizures, they have become widely prescribed drugs. Many of these uses are off-label for psychiatric indications, and there is increasing concern about their safety, so it is particularly important to have good evidence to justify this usage. We conducted a systematic review and meta-analysis of the evidence for three of their common psychiatric uses: bipolar disorder, anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 84 publications
(105 reference statements)
0
30
0
4
Order By: Relevance
“…28 There is evidence to suggest efficacy of GABA in the treatment of anxiety disorders. 29,30 In a systematic review and meta-analysis by Hong et al, 29 GABA (gabapentin, pregabalin) were effective in the treatment of anxiety disorders, including generalized anxiety disorder, social anxiety disorder, and preoperative anxiety disorder. A 1-year open label study by Montgomery et al 31 found that long-term use of pregabalin is relatively safe for the treatment of anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…28 There is evidence to suggest efficacy of GABA in the treatment of anxiety disorders. 29,30 In a systematic review and meta-analysis by Hong et al, 29 GABA (gabapentin, pregabalin) were effective in the treatment of anxiety disorders, including generalized anxiety disorder, social anxiety disorder, and preoperative anxiety disorder. A 1-year open label study by Montgomery et al 31 found that long-term use of pregabalin is relatively safe for the treatment of anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of ‘sun downing’, a state of confusion and anxiety, often accompanied by aggressive behaviors and sleep problems that are triggered by little sunlight, is often a symptom that not only affects the patient's but also the caregiver's quality of life. GBP has been employed by psychiatrists in various anxiety and insomnia states [53] and is one of the most commonly prescribed ASMs in this population [32]. Low-dose GBP has been shown to have similar seizure control as LTG [11], and it is our experience that a slightly higher dose given in the evening can help ‘sun downing’ while also controlling seizures.…”
Section: Treatment Strategies Of Epilepsy In People Living With Neuro...mentioning
confidence: 97%
“…Nie ma jednoznacznych dowodów na terapię gabapentyną w depresji, profilaktyce PTSD (z ang. post-traumatic stress disorder), lub innych rodzajach nadużywania substancji psychoaktywnych [18,3].…”
Section: Gabapentyna W Leczeniu Zaburzeń Lękowych I Innych Schorzeń P...unclassified